Effects of Melatonin on Neurobehavior and Cognition in a Cerebral Palsy Model of plppr5−/− Mice - Sun, Yuxiao; Ma, Liya; Jin, Meifang; Zheng, Yuqin; Wang, Dandan; Ni, Hong (Frontiers in Endocrinology, 2021)
Cerebral palsy (CP), a group of clinical syndromes caused bynonprogressive brain damage in the developing fetus or infant, is one of the most common causes of lifelong physical disability in children in most countries.We used plppr5 knockout (plppr5-/-) mice and their wild-type littermates to establisha model of hypoxicischemic brain injury (HI) to further explore the effects of melatonin on brain injury and the role of plppr5 in this treatment in an HI model, which mainly focuses on cognition, exercise, learning and memory. In these experiments, we found that there was a significant interaction between genotype and treatment in novel object recognition tests, surface righting reflex tests and forelimb suspension reflex tests, which represent learning and memory, motor function and coordination, and the forelimb grip of the mice, respectively. However, a significant main effect of genotype and treatment on performance in all behavioral tests were observed. Specifically, wild-type mice with HI injury performed better than plppr5-/- mice, regardless of treatment with melatonin or vehicle. Moreover, treatment with melatonin could improve behavior in the tests for wild-type mice with HI injury, but not for plppr5-/- mice. This study showed that plppr5 knockout aggravated HI damage and partially weakened the neuroprotection of melatonin in some aspects (such as novel object recognition tests and partial nerve reflexes)